LIPOID PNEUMONIA IN CHILDREN IN A CASE OF ACUTE POISONING WITH IGNITE LIQUID (Herald of the National Children's Medical Center, 2022)
This article describes a case of poisoning with ignition 0uid, which led to the development of lipoid pneumonia in a child
Keywords: poisoning; lipoid pneumonia; child